Remote Research Real Users, Real Time, Real Research - Bolt, Nate (Rosenfeld Media, 2012)
Remote studies allow you to recruit subjects quickly, cheaply, and immediately, and give you the opportunity to observe users as they behave naturally in their own environment. In Remote Research, Nate Bolt and Tony Tulathimutte teach you how to design and conduct remote research studies, top to bottom, with little more than a phone and a laptop.